A study to examine the relationship between mothers’ psychosocial status and pregnancy outcome - Patharkar, Minal Milind (BOHR Journal of Obstetrics and Gynaecology, 2023)
Introduction: Pregnancy is the most wonderful experience of a woman’s life. A mother’s physical fitness is just as important as her mental health. A non-experimental and correlational study was conducted to examine the relationship between mothers’ psychosocial status and pregnancy outcome among 50 antenatal mothers in their third trimester. The aim: of the study is to assess the psychosocial status of antenatal care (ANC) mothers, assess the pregnancy outcome, and find out the correlation between psychosocial status and pregnancy outcome. Result: In this study, using the ALPHA scale to assess the psychosocial status of antenatal mothers, the majority of them had a higher psychosocial score, and some had a middle psychosocial score, but none had a low psychosocial score. Conclusion: From this study, we conclude that there was an association between psychosocial status and pregnancy outcome.